The influence of perceived behaviour control, attitude and empowerment on reported condom use and intention to use condoms among adolescents in rural Tanzania. Issue 1 (December 2015) - Kalolo, Albino; Kibusi, Stephen
Abstract Background Despite the declining trends of Human immunodeficiency virus (HIV) infection in Sub-Saharan Africa (SSA), unsafe sexual behaviours among adolescents still represent a public health challenge. It is important to understand factors acting at different levels to influence sexual behaviour among adolescents. This study examined the influence of perceived behaviour control, subjective norms, attitudes and empowerment on intention to use condoms and reported use of condoms among adolescents in rural Tanzania. Methods We used a questionnaire to collect data from 403 adolescents aged 14 through 19 years from nine randomly selected secondary schools in the Newala district located in the Southern part of Tanzania. The self-administered questionnaire collected information on sexual practices and factors such as attitudes, subjective norms, perceived behaviour control and empowerment. Binary logistic regression was performed to identify factors associated with intention to use and reported use of condoms. Results Sexually active adolescents constituted 40.6 % of the sample, among them 49.7 % did not use a condom at last sexual intercourse and 49.8 % had multiple sex partners. Many (85 %) of sexually active respondents had their sexual debut between the ages of 14 to 17 years. Girls became sexually active earlier than boys. Perceived behaviour control predicted intentions to use condoms (AOR = 3.059, 95 % CI 1.324-7.065), thus demonstrating its importance in the decision to use a condom. Empowerment (odds ratio = 3.694, 95 % CI 1.295-10.535) and a positive attitude (AOR = 3.484, 95 % CI 1.132-10.72) predicted reported condom use, thus turning the decision to actions. Subjective norms had only indirect effects on intention and reported use of condoms. Conclusion The findings suggest that unsafe sex practices are prevalent among school adolescents in rural areas of Tanzania. Perceived behaviour control and positive attitudes predict intensions to use condoms whereas empowerment predicts reported condom use. The findings may imply that safe sex promotion interventions that simultaneously address socio-cognitive and ecological determinants of sexual behaviours may improve adolescents' safe sex behaviours.